A new approach to the optimisation of zinc electrolyte cold purification process by Taguchi's method. (July 2014) - Behnajady, B.; Balesini, A. A.; Moghaddam, J.
Abstract : The neutralised zinc sulfate solution obtained from hydrometallurgical process of Angouran zinc concentrate has cadmium, nickel and cobalt impurities that must be purified before electrowinning. Therefore, cadmium and nickel are usually cemented out by addition of zinc dust under cold purification conditions. The present research aims to introduce a new technique for determination of effective parameters and optimisation of zinc electrolyte cold purification process using statistical design of experiments. The Taguchi's method, based on orthogonal array design (OAD), was used to arrange the experiments. The experimental conditions addressed in the study were: the temperature range of 45–65°C for reaction temperature ( T ), one to five series for zinc dust particle size distributions ( S ), 15–75 min for reaction time ( t ), 1–2⋅5 g L −1 for zinc powder concentration ( M ), and 200–600 rev min −1 ( R ) for stirring speed. Optimum conditions for cold purification obtained in this study were T 4 (60°C), S 1 (series 1), t 3 (45 min), M 5 (2⋅5 g L −1 ), and R 1 (200 rev min −1 ). La solution neutralisée de sulfate de zinc, obtenue à partir du procédé d'hydrométallurgie du concentré de zinc provenant d'Angouran, contient des impuretés de cadmium, de nickel et de cobalt que l'on doit purifier avant l'extraction électrolytique. Habituellement, on extrait le cadmium et le nickel par cémentation par addition de poudre de zinc sous des conditions de purification à froid. La recherche actuelle a pour but d'introduire une nouvelle technique pour la détermination des paramètres efficaces et pour l'optimisation du procédé de purification à froid de l'électrolyte de zinc en utilisant un plan d'expérience statistique. On a utilisé la méthode de Taguchi, basée sur un concept d'arrangement orthogonal (OAD), pour planifier les expériences. Les conditions expérimentales examinées dans l'étude incluaient la gamme de température de 45 à 65°C pour la température de réaction ( T ), une série d'une à cinq distributions de taille de particule de la poudre de zinc ( S ), de 15 à 75 min pour le temps de réaction ( t ), de 1 à 2⋅5 g L −1 pour la concentration de la poudre de zinc ( M ) et de 200 à 600 rpm ( R) pour la vitesse d'agitation. Les conditions optimales obtenues dans cette étude pour la purification à froid étaient de T 4 (60°C), S 1 (série 1), t 3 (45 min), M 5 (2⋅5 g L −1 ) et R 1 (200 rpm).